Company's diversification strategy and crash risk stock prices emphasizing operational slack and management ability - Majid Moradi; Roqaye Talebi; Hamid Reza Pakdaman (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Investors significantly value the risk of falling and consider the risk of falling as an important pricing factor. The negative price changes are also affected by managers' ability to choose strategies and properly implement the company's operations. Therefore, this research investigates the relationship between the company's diversification strategy and the risk of falling stock prices, emphasizing the weakness of operations and management's ability during the year 2016-2022.Methodology: The multivariable regression method and the financial information of 129 companies admitted to the Tehran Stock Exchange have been used to test the research hypotheses. The research hypotheses were rejected or proved by applying appropriate statistical methods to generalize the results. The financial data was collected in Excel to form a database and then analyzed using Eviuse software to test the research hypotheses.Findings: The research results showed that according to the first hypothesis, the company's diversification strategy has a negative relationship with the risk of falling stock prices, which is confirmed. Also, the second hypothesis that operational laxity strengthens the negative relationship between diversification strategy and the risk of falling stock prices is not confirmed. And according to the third hypothesis, management ability strengthens the negative relationship between diversification strategy and the risk of falling stock prices, not confirmed.Originality/Value: From the aspect of research innovation, we can mention the following: first, it showed that the diverse operations of companies act as a factor in reducing the risk of their collapse, thereby clarifying a new reason for companies to expand their operational scope. Furthermore, it showed that the effectiveness of diversification is consistent with the evidence provided by the literature on bad news hoarding theory; that is, diversification can reduce the negative effects of bad news. It contributes to the fall risk literature. Such insights open a new avenue for future research to investigate how to reduce the risk of collapse through the strategic design of companies' operations and production. Third, the prevailing consensus among management scholars is that diversification is essential regarding economic performance and risk reduction. The findings of this study enhance the existing understanding of corporate diversification on bankruptcy risk. Fourth, the present study considers a set of contextual factors that moderate primary communication. This analysis provides a detailed look at the possible intervening factors between diversity and fall risk.